The effects of partisan framing on COVID-19 attitudes: Experimental evidence from early and late pandemic - Amber Wichowsky; Meghan Condon (Research & Politics, 2022)
Political polarization has dominated news coverage of Americans’ responses to the COVID-19 pandemic. In this research note, we report findings from two experimental studies, in which we present respondents with news stories about COVID-19 mitigation measures that emphasize partisan difference or accord. The stories present the same numeric facts about public opinion, but highlight either the partisan gap that existed at the time of the study, or the fact that large majorities of both Republicans and Democrats supported the measures at the time. Results from our first study, conducted late April 2020, show that a media frame drawing attention to shared concern across party lines produced a less polarized response to social-distancing restrictions than a frame that drew attention to partisan difference. Our findings suggest that the extensive media coverage about the red-blue divide in COVID-19 opinions reinforced partisan polarization. These results, however, did not replicate in a second study conducted much later in the pandemic. Qualitative data collected across the two studies demonstrate the degree to which polarization had rapidly become a dominant narrative in Americans’ thinking about COVID-19.